An integrative approach to species discrimination in the Anagrus atomus group sensu stricto (Hymenoptera: Mymaridae), with a description of a new species. Issue 6 (2nd November 2017) - Nugnes, Francesco; Bernardo, Umberto; Viggiani, Gennaro
Abstract : Egg parasitoids of the genus Anagrus Haliday (Hymenoptera: Mymaridae) are natural enemies of many pests around the world. We used an integrative approach to characterize some species belonging to the Anagrus atomus group, using specimens reared from leafhoppers infesting some Lamiaceae. Starting from morphological identifications based on available keys, we carried out a multi-locus genetic characterization using phylogenetic and species delimitation analyses, and integrated it with biological and morphometric evidence. This approach revealed the existence of a new species, A. nepetellae sp. nov., here described along with its phenological traits. The approach also allowed us to characterize the expected taxonomic stability of other putative species within the group. We propose two new species groups called the atomus group sensu stricto and the vilis group, with the goal of streamlining the taxonomy of the atomus group. We also present a key for the identification of females of the European species of the atomus group sensu stricto . Some specimens show heterozygosity in 28S-D2 sequences, suggesting hybridization between A. atomus and A. nepetellae, which, if it is common between other species as well, could partly explain the taxonomic problems in the genus Anagrus . DNA sequencing of specimens reared by the same biofactory at different times suggests involuntary contamination leading to the displacement of a laboratory strain of A. atomus by A. nepetellae, which may have resulted from undetected partial reproductive compatibility.http://zoobank.org/urn:lsid:zoobank.org:pub:DFCD7654-5AA5-4E4F-AE48-24377BAACEFE